a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
B(b(x1)) → C(c(x1))
C(c(x1)) → C(b(x1))
B(b(x1)) → C(c(c(x1)))
B(b(x1)) → C(x1)
B(b(x1)) → C(c(c(c(x1))))
C(c(x1)) → B(x1)
C(c(x1)) → A(c(b(x1)))
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B(b(x1)) → C(c(x1))
C(c(x1)) → C(b(x1))
B(b(x1)) → C(c(c(x1)))
B(b(x1)) → C(x1)
B(b(x1)) → C(c(c(c(x1))))
C(c(x1)) → B(x1)
C(c(x1)) → A(c(b(x1)))
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B(b(x1)) → C(c(x1))
C(c(x1)) → C(b(x1))
B(b(x1)) → C(c(c(x1)))
B(b(x1)) → C(x1)
B(b(x1)) → C(c(c(c(x1))))
C(c(x1)) → B(x1)
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
C(c(b(x0))) → C(c(c(c(c(x0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS Reverse
↳ QTRS Reverse
B(b(x1)) → C(c(x1))
B(b(x1)) → C(c(c(x1)))
B(b(x1)) → C(c(c(c(x1))))
B(b(x1)) → C(x1)
C(c(x1)) → B(x1)
C(c(b(x0))) → C(c(c(c(c(x0)))))
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
B(b(x1)) → C(c(x1))
B(b(x1)) → C(c(c(x1)))
B(b(x1)) → C(c(c(c(x1))))
B(b(x1)) → C(x1)
C(c(x1)) → B(x1)
C(c(b(x0))) → C(c(c(c(c(x0)))))
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
B(b(x1)) → C(c(x1))
B(b(x1)) → C(c(c(x1)))
B(b(x1)) → C(c(c(c(x1))))
B(b(x1)) → C(x1)
C(c(x1)) → B(x1)
C(c(b(x0))) → C(c(c(c(c(x0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → a(c(b(x)))
B(b(x)) → C(c(x))
B(b(x)) → C(c(c(x)))
B(b(x)) → C(c(c(c(x))))
B(b(x)) → C(x)
C(c(x)) → B(x)
C(c(b(x))) → C(c(c(c(c(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → a(c(b(x)))
B(b(x)) → C(c(x))
B(b(x)) → C(c(c(x)))
B(b(x)) → C(c(c(c(x))))
B(b(x)) → C(x)
C(c(x)) → B(x)
C(c(b(x))) → C(c(c(c(c(x)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → a(c(b(x)))
B(b(x)) → C(c(x))
B(b(x)) → C(c(c(x)))
B(b(x)) → C(c(c(c(x))))
B(b(x)) → C(x)
C(c(x)) → B(x)
C(c(b(x))) → C(c(c(c(c(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → a(c(b(x)))
B(b(x)) → C(c(x))
B(b(x)) → C(c(c(x)))
B(b(x)) → C(c(c(c(x))))
B(b(x)) → C(x)
C(c(x)) → B(x)
C(c(b(x))) → C(c(c(c(c(x)))))
C1(c(x)) → A(x)
B1(B(x)) → C1(c(c(C(x))))
B1(b(x)) → C1(c(c(c(x))))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
B1(b(x)) → C1(c(c(x)))
C1(c(x)) → B1(c(a(x)))
B1(B(x)) → C1(c(C(x)))
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(B(x)) → C1(C(x))
C1(c(x)) → C1(a(x))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
C1(c(x)) → A(x)
B1(B(x)) → C1(c(c(C(x))))
B1(b(x)) → C1(c(c(c(x))))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
B1(b(x)) → C1(c(c(x)))
C1(c(x)) → B1(c(a(x)))
B1(B(x)) → C1(c(C(x)))
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(B(x)) → C1(C(x))
C1(c(x)) → C1(a(x))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(B(x)) → C1(c(c(C(x))))
B1(b(x)) → C1(c(c(x)))
B1(b(x)) → C1(c(c(c(x))))
C1(c(x)) → B1(c(a(x)))
B1(B(x)) → C1(c(C(x)))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
C1(c(x)) → C1(a(x))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
C1(c(a(x0))) → B1(c(x0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(B(x)) → C1(c(c(C(x))))
B1(b(x)) → C1(c(c(c(x))))
B1(b(x)) → C1(c(c(x)))
B1(B(x)) → C1(c(C(x)))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → B1(c(x0))
C1(c(x)) → C1(a(x))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
C1(c(a(x0))) → C1(x0)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(B(x)) → C1(c(c(C(x))))
B1(b(x)) → C1(c(c(x)))
B1(b(x)) → C1(c(c(c(x))))
B1(B(x)) → C1(c(C(x)))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(B(x0)) → C1(B(x0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(B(x0)) → C1(B(x0))
B1(B(x)) → C1(c(c(C(x))))
B1(b(x)) → C1(c(c(c(x))))
B1(b(x)) → C1(c(c(x)))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(B(x)) → C1(c(c(C(x))))
B1(b(x)) → C1(c(c(x)))
B1(b(x)) → C1(c(c(c(x))))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(B(x0)) → C1(c(B(x0)))
B1(B(y0)) → C1(b(c(a(C(y0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x)) → C1(c(c(c(x))))
B1(b(x)) → C1(c(c(x)))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(B(x0)) → C1(c(B(x0)))
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
B1(B(y0)) → C1(b(c(a(C(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x)) → C1(c(c(x)))
B1(b(x)) → C1(c(c(c(x))))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(c(C(x))) → C1(c(c(C(x))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(c(C(y0))) → C1(b(c(a(C(y0)))))
B1(c(C(x0))) → C1(c(B(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x)) → C1(c(c(c(x))))
B1(b(x)) → C1(c(c(x)))
B1(c(C(y0))) → C1(b(c(a(C(y0)))))
B1(c(C(x0))) → C1(c(B(x0)))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x)) → C1(c(c(x)))
B1(b(x)) → C1(c(c(c(x))))
B1(c(C(x))) → C1(c(C(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(c(C(x0))) → C1(B(x0))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x)) → C1(c(c(c(x))))
B1(b(x)) → C1(c(c(x)))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(c(C(x0))) → C1(B(x0))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x)) → C1(c(c(x)))
B1(b(x)) → C1(c(c(c(x))))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(C(x0))) → C1(c(c(B(x0))))
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(b(y0)) → C1(b(c(a(c(y0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(c(c(x)))
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(C(x0))) → C1(c(c(B(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
B1(b(C(x0))) → C1(c(B(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(x)
B1(b(x)) → C1(c(x))
B1(b(C(x0))) → C1(c(c(B(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
C1(c(a(x0))) → C1(x0)
B1(b(C(x0))) → C1(c(B(x0)))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(x)
B1(c(C(x))) → C1(c(c(c(C(x)))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(C(x0))) → C1(c(c(B(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(c(C(y0))) → C1(c(b(c(a(C(y0))))))
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(x)
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(c(C(y0))) → C1(c(b(c(a(C(y0))))))
B1(b(x)) → C1(c(x))
B1(b(C(x0))) → C1(c(c(B(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
C1(c(a(x0))) → C1(x0)
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(x)
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(C(x0))) → C1(c(c(B(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(b(C(y0))) → C1(b(c(a(B(y0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(C(y0))) → C1(b(c(a(B(y0)))))
B1(b(x)) → C1(x)
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
C1(c(a(x0))) → C1(x0)
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x0)) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(x)
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(b(a(x0))) → C1(c(b(c(x0))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(x0)) → C1(b(c(a(x0))))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
B1(b(a(x0))) → C1(c(b(c(x0))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(b(a(x0))) → C1(b(c(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(a(x0))) → C1(b(c(x0)))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(b(c(x0))) → C1(c(b(c(a(x0)))))
B1(b(x)) → C1(c(x))
B1(b(a(x0))) → C1(c(b(c(x0))))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(a(x0))) → C1(b(c(x0)))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(c(C(x0))) → C1(c(c(B(x0))))
B1(b(a(x0))) → C1(c(b(c(x0))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(c(C(y0))) → C1(b(c(a(B(y0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(c(C(y0))) → C1(b(c(a(B(y0)))))
B1(b(a(x0))) → C1(b(c(x0)))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(b(x)) → C1(c(x))
B1(b(a(x0))) → C1(c(b(c(x0))))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(a(x0))) → C1(b(c(x0)))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(c(C(y0))) → C1(b(c(a(c(C(y0))))))
B1(b(a(x0))) → C1(c(b(c(x0))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1(c(C(x0))) → C1(b(c(a(B(x0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(c(C(x0))) → C1(b(c(a(B(x0)))))
B1(b(a(x0))) → C1(b(c(x0)))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(b(x)) → C1(c(x))
B1(b(a(x0))) → C1(c(b(c(x0))))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(a(x0))) → C1(b(c(x0)))
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(b(a(x0))) → C1(c(b(c(x0))))
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
B1(b(a(x0))) → C1(b(c(x0)))
B1(b(a(x0))) → C1(c(b(c(x0))))
Used ordering: Polynomial Order [21,25] with Interpretation:
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
C1(c(a(x0))) → B1(c(x0))
B1(b(y0)) → C1(b(c(a(c(y0)))))
POL( C(x1) ) = max{0, -1}
POL( c(x1) ) = max{0, -1}
POL( B(x1) ) = max{0, -1}
POL( a(x1) ) = 1
POL( B1(x1) ) = x1
POL( b(x1) ) = x1
POL( C1(x1) ) = max{0, -1}
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(c(C(x))) → c(c(c(c(C(x)))))
b(b(x)) → c(c(c(c(x))))
b(B(x)) → c(c(c(C(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → C(x)
c(C(x)) → B(x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
C1(c(a(x0))) → B1(c(x0))
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
B1(b(y0)) → C1(b(c(a(c(y0)))))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
B1.0(b.0(c.0(a.1(x0)))) → C1.0(c.0(b.0(c.1(x0))))
B1.0(b.0(c.0(x0))) → C1.0(c.0(c.0(b.0(c.1(a.0(x0))))))
B1.0(b.1(y0)) → C1.0(b.0(c.1(a.0(c.1(y0)))))
C1.0(c.0(a.1(x0))) → B1.0(c.1(x0))
B1.0(b.0(c.1(a.0(x0)))) → C1.0(c.0(b.0(c.0(x0))))
C1.0(c.1(a.0(x0))) → B1.0(c.0(x0))
C1.0(c.0(a.1(x0))) → C1.1(x0)
B1.0(b.0(x)) → C1.0(c.0(x))
B1.0(b.0(c.1(x0))) → C1.0(c.0(c.0(b.0(c.0(a.1(x0))))))
C1.0(c.1(a.0(x0))) → C1.0(x0)
B1.0(b.1(x)) → C1.1(x)
B1.0(b.1(x)) → C1.0(c.1(x))
B1.0(b.0(y0)) → C1.0(b.0(c.1(a.0(c.0(y0)))))
B1.0(b.0(x)) → C1.0(x)
b.0(c.0(C.0(x))) → c.0(c.0(c.0(c.0(C.0(x)))))
c.0(C.0(x)) → B.0(x)
b.0(B.0(x)) → C.0(x)
b.0(B.0(x)) → c.0(c.0(C.0(x)))
c.0(c.1(x)) → b.0(c.0(a.1(x)))
b.0(b.1(x)) → c.0(c.0(c.0(c.1(x))))
c.0(C.1(x)) → B.1(x)
c.0(c.0(x)) → b.0(c.1(a.0(x)))
b.0(c.0(C.1(x))) → c.0(c.0(c.0(c.0(C.1(x)))))
b.0(B.1(x)) → C.1(x)
b.0(B.0(x)) → c.0(c.0(c.0(C.0(x))))
b.0(B.1(x)) → c.0(c.0(C.1(x)))
a.1(a.0(x)) → x
a.0(a.1(x)) → x
b.0(B.0(x)) → c.0(C.0(x))
b.0(b.0(x)) → c.0(c.0(c.0(c.0(x))))
b.0(B.1(x)) → c.0(c.0(c.0(C.1(x))))
b.0(B.1(x)) → c.0(C.1(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ SemLabProof2
↳ QTRS Reverse
↳ QTRS Reverse
B1.0(b.0(c.0(a.1(x0)))) → C1.0(c.0(b.0(c.1(x0))))
B1.0(b.0(c.0(x0))) → C1.0(c.0(c.0(b.0(c.1(a.0(x0))))))
B1.0(b.1(y0)) → C1.0(b.0(c.1(a.0(c.1(y0)))))
C1.0(c.0(a.1(x0))) → B1.0(c.1(x0))
B1.0(b.0(c.1(a.0(x0)))) → C1.0(c.0(b.0(c.0(x0))))
C1.0(c.1(a.0(x0))) → B1.0(c.0(x0))
C1.0(c.0(a.1(x0))) → C1.1(x0)
B1.0(b.0(x)) → C1.0(c.0(x))
B1.0(b.0(c.1(x0))) → C1.0(c.0(c.0(b.0(c.0(a.1(x0))))))
C1.0(c.1(a.0(x0))) → C1.0(x0)
B1.0(b.1(x)) → C1.1(x)
B1.0(b.1(x)) → C1.0(c.1(x))
B1.0(b.0(y0)) → C1.0(b.0(c.1(a.0(c.0(y0)))))
B1.0(b.0(x)) → C1.0(x)
b.0(c.0(C.0(x))) → c.0(c.0(c.0(c.0(C.0(x)))))
c.0(C.0(x)) → B.0(x)
b.0(B.0(x)) → C.0(x)
b.0(B.0(x)) → c.0(c.0(C.0(x)))
c.0(c.1(x)) → b.0(c.0(a.1(x)))
b.0(b.1(x)) → c.0(c.0(c.0(c.1(x))))
c.0(C.1(x)) → B.1(x)
c.0(c.0(x)) → b.0(c.1(a.0(x)))
b.0(c.0(C.1(x))) → c.0(c.0(c.0(c.0(C.1(x)))))
b.0(B.1(x)) → C.1(x)
b.0(B.0(x)) → c.0(c.0(c.0(C.0(x))))
b.0(B.1(x)) → c.0(c.0(C.1(x)))
a.1(a.0(x)) → x
a.0(a.1(x)) → x
b.0(B.0(x)) → c.0(C.0(x))
b.0(b.0(x)) → c.0(c.0(c.0(c.0(x))))
b.0(B.1(x)) → c.0(c.0(c.0(C.1(x))))
b.0(B.1(x)) → c.0(C.1(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesReductionPairsProof
↳ SemLabProof2
↳ QTRS Reverse
↳ QTRS Reverse
C1.0(c.1(a.0(x0))) → B1.0(c.0(x0))
B1.0(b.0(x)) → C1.0(c.0(x))
B1.0(b.0(c.1(x0))) → C1.0(c.0(c.0(b.0(c.0(a.1(x0))))))
C1.0(c.1(a.0(x0))) → C1.0(x0)
B1.0(b.1(x)) → C1.0(c.1(x))
B1.0(b.0(c.0(x0))) → C1.0(c.0(c.0(b.0(c.1(a.0(x0))))))
B1.0(b.0(c.1(a.0(x0)))) → C1.0(c.0(b.0(c.0(x0))))
B1.0(b.0(x)) → C1.0(x)
b.0(c.0(C.0(x))) → c.0(c.0(c.0(c.0(C.0(x)))))
c.0(C.0(x)) → B.0(x)
b.0(B.0(x)) → C.0(x)
b.0(B.0(x)) → c.0(c.0(C.0(x)))
c.0(c.1(x)) → b.0(c.0(a.1(x)))
b.0(b.1(x)) → c.0(c.0(c.0(c.1(x))))
c.0(C.1(x)) → B.1(x)
c.0(c.0(x)) → b.0(c.1(a.0(x)))
b.0(c.0(C.1(x))) → c.0(c.0(c.0(c.0(C.1(x)))))
b.0(B.1(x)) → C.1(x)
b.0(B.0(x)) → c.0(c.0(c.0(C.0(x))))
b.0(B.1(x)) → c.0(c.0(C.1(x)))
a.1(a.0(x)) → x
a.0(a.1(x)) → x
b.0(B.0(x)) → c.0(C.0(x))
b.0(b.0(x)) → c.0(c.0(c.0(c.0(x))))
b.0(B.1(x)) → c.0(c.0(c.0(C.1(x))))
b.0(B.1(x)) → c.0(C.1(x))
The following rules are removed from R:
B1.0(b.1(x)) → C1.0(c.1(x))
Used ordering: POLO with Polynomial interpretation [25]:
b.0(b.1(x)) → c.0(c.0(c.0(c.1(x))))
POL(B.0(x1)) = x1
POL(B.1(x1)) = x1
POL(B1.0(x1)) = x1
POL(C.0(x1)) = x1
POL(C.1(x1)) = x1
POL(C1.0(x1)) = x1
POL(a.0(x1)) = x1
POL(a.1(x1)) = x1
POL(b.0(x1)) = x1
POL(b.1(x1)) = 1 + x1
POL(c.0(x1)) = x1
POL(c.1(x1)) = x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesReductionPairsProof
↳ QDP
↳ SemLabProof2
↳ QTRS Reverse
↳ QTRS Reverse
C1.0(c.1(a.0(x0))) → B1.0(c.0(x0))
B1.0(b.0(x)) → C1.0(c.0(x))
B1.0(b.0(c.1(x0))) → C1.0(c.0(c.0(b.0(c.0(a.1(x0))))))
C1.0(c.1(a.0(x0))) → C1.0(x0)
B1.0(b.0(c.0(x0))) → C1.0(c.0(c.0(b.0(c.1(a.0(x0))))))
B1.0(b.0(c.1(a.0(x0)))) → C1.0(c.0(b.0(c.0(x0))))
B1.0(b.0(x)) → C1.0(x)
c.0(C.0(x)) → B.0(x)
b.0(c.0(C.0(x))) → c.0(c.0(c.0(c.0(C.0(x)))))
b.0(B.0(x)) → c.0(c.0(C.0(x)))
b.0(B.0(x)) → c.0(c.0(c.0(C.0(x))))
b.0(B.1(x)) → c.0(c.0(C.1(x)))
c.0(c.1(x)) → b.0(c.0(a.1(x)))
b.0(b.0(x)) → c.0(c.0(c.0(c.0(x))))
b.0(B.1(x)) → c.0(c.0(c.0(C.1(x))))
b.0(c.0(C.1(x))) → c.0(c.0(c.0(c.0(C.1(x)))))
c.0(C.1(x)) → B.1(x)
c.0(c.0(x)) → b.0(c.1(a.0(x)))
a.0(a.1(x)) → x
a.1(a.0(x)) → x
b.0(B.0(x)) → C.0(x)
b.0(B.1(x)) → C.1(x)
b.0(B.0(x)) → c.0(C.0(x))
b.0(B.1(x)) → c.0(C.1(x))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QTRS Reverse
↳ QTRS Reverse
B1(b(c(x0))) → C1(c(c(b(c(a(x0))))))
B1(b(x)) → C1(x)
B1(b(x)) → C1(c(x))
C1(c(a(x0))) → C1(x0)
B1(b(c(a(x0)))) → C1(c(b(c(x0))))
C1(c(a(x0))) → B1(c(x0))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
b(B(x)) → c(C(x))
b(B(x)) → c(c(C(x)))
b(B(x)) → c(c(c(C(x))))
b(B(x)) → C(x)
c(C(x)) → B(x)
b(c(C(x))) → c(c(c(c(C(x)))))
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
a(a(x1)) → x1
b(b(x1)) → c(c(c(c(x1))))
c(c(x1)) → a(c(b(x1)))
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
a(a(x)) → x
b(b(x)) → c(c(c(c(x))))
c(c(x)) → b(c(a(x)))